The Terror of Data Dissemination Due to Online Loan Default Perspective of Law Number 11 of 2008 concerning Electronic Information and Transactions (Case Study of Online Loan Customers in Medan City) - Safira Safira; Syofiaty Lubis (UNIVERSITAS PAKUAN, 2023)
The terror of data dissemination when customers default on online loans is indeed very troubling. Law Number 11 of 2008 concerning Electronic Information and Transactions considers that this act violates the law. However, in its implementation in the field, the ITE Law is not very satisfactory in protecting defaulted customers from the terror of spreading data. In this study using empirical juridical methods with a statutory approach and a case approach. The results of this study prove that the terror of spreading data for defaulted customers is usually done by calling emergency numbers first to hijacking galleries and distributing photos of ID cards at the time of submission and also selfies when filing. This terror is also carried out on the numbers of companies where customers work so that it is not uncommon for customers to be fired because of the terror of spreading the data. The factor of indebted customers on online loan platforms in Medan City is due to the ease of selecting loans themselves, due to urgent economic needs, and very minimal financial literacy makes loan customers always trapped in the trap of borrowers who sometimes want to leak data and threaten when billing. In its implementation in the field, Law Number 11 of 2008 concerning Electronic Information and Transactions is not carried out optimally considering the high terror of data distribution carried out by online loans currently in Indonesian technology findusia. That is, the ITE Law is indeed protecting the public from the spread of data, but in its implementation in the field the ITE Law itself is not so strong in protecting the public from the terror of spreading data. This is also because there are rubber articles that have ambiguous explanations and articles whose implementation in the field can be compromised